2016
DOI: 10.1186/s13568-016-0275-z
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of the white-rot fungus Anthracophyllum discolor to degrade the herbicide atrazine

Abstract: Herbicides cause environmental concerns because they are toxic and accumulate in the environment, food products and water supplies. There is a need to develop safe, efficient and economical methods to remove them from the environment, often by biodegradation. Atrazine is such herbicide. White-rot fungi have the ability to degrade herbicides of potential utility. This study formulated a novel pelletized support to immobilize the white-rot fungus Anthracophyllum discolor to improve its capability to degrade the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…LEJ701 and LEJ702 (Ellegaard‐Jensen et al, 2013). Elgueta et al (2016) formulated a novel pelletized support to immobilize Anthracophyllum discolor , a white rot fungus, for improving its ability to degrade the atrazine, a herbicide, by a bio‐purification system and for generating three pelletized supports (F1, F2, and F3), different proportions of starch, sawdust, flaxseed, and corn meal were used. The most effective system was F1 as it provided great manganese peroxidase activity and fungal viability (Elgueta et al, 2016).…”
Section: Mycoremediation Of Organic Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…LEJ701 and LEJ702 (Ellegaard‐Jensen et al, 2013). Elgueta et al (2016) formulated a novel pelletized support to immobilize Anthracophyllum discolor , a white rot fungus, for improving its ability to degrade the atrazine, a herbicide, by a bio‐purification system and for generating three pelletized supports (F1, F2, and F3), different proportions of starch, sawdust, flaxseed, and corn meal were used. The most effective system was F1 as it provided great manganese peroxidase activity and fungal viability (Elgueta et al, 2016).…”
Section: Mycoremediation Of Organic Pollutantsmentioning
confidence: 99%
“…intermedia DP8-1(Wang et al, 2017), Mortierella sp.LEJ701 and LEJ702 (Ellegaard-Jensen et al, 2013) Elgueta et al (2016). formulated a novel pelletized support to immobilize Anthracophyllum discolor, a white rot fungus, for improving its ability to degrade the atrazine, a herbicide, by a bio-purification system and for generating three pelletized supports (F1, F2, and F3), different proportions of starch, sawdust, flaxseed, and corn meal were used.…”
mentioning
confidence: 99%
“…Laccase was extracted according to Elgueta et al [54], and the activity was measured by mixing 0.5 mL of the extracted sample, 0.25 mL of 100 mM glycine (pH 3.0), and 0.25 mL of 4 mM ABTS, and incubating at 25 • C for 5 min before the measurement. Then, 1 mL of the sample was used for Laccase determination by spectrophotometry at 405 nm in a BK-UV1800 spectrophotometer (Biobase).…”
Section: Laccasementioning
confidence: 99%
“…Jayabarath et al [ 53 ] selected 319 actinomycetes from saline soils of Sangli District (Maharashtra) for carbofuran tolerance test, while only the seven strains of Streptomyces alanosinicus, Streptoverticillium album, Nocardia farcinia, Streptomyces atratus, Nocardia vaccini, Nocardia amarae, and Micromonospora chalcea can grow and degrade pesticides very well. Elgueta et al [ 54 ] used white-rot fungi to study the degradation of atrazine and found that the half-life of atrazine decreased to six days. Besides, Kabra et al [ 55 ] studied the ability of green microalga Chlamydomonas mexicana to degrade atrazine and found that microalgae could effectively degrade atrazine by accumulating atrazine in cells and then degrading it, reaching a degradation rate of 14–36%.…”
Section: Research On the Progress Of Microbial-degradation Of Pestmentioning
confidence: 99%